Cross-regional engagement between ASEAN and Latin America: defining barriers to trade in the Malaysia-Chile partnership - Devadason, E.S.; Chandran, V.G.R.; Mubarik, S. (2015)
This study seeks to compare bilateral export potential estimates in the Malaysia-Chile partnership within the context of the emerging region of Latin America and the Caribbean (LAC) and identify barriers to trade, to provide insights into bilateral market access for exporters. Clearly, the empirical findings suggest over trading in the major exporting sectors from both sides, since the export basket is also concentrated both ways in the Malaysia-Chile trade. Through the interviews, fewer restrictions are reported by the various stakeholders, as the extent of trade engagement is still somewhat low. Instead, the challenges identified within specific sub-sectors from both sides relate mainly to procedures set to secure compliance. They mostly indicate adherence to labeling requirements for food products. More importantly, this study strongly recommends the direct involvement of the business community of Malaysia in cross-regional initiatives to identify opportunities for creating supply chains in Chile for specific sectors, namely in electronics, furniture and base metals.